Code and Clay, Data and Dirt : Five Thousand Years of Urban Media - Mattern, Shannon Christine (Book collections on Project MUSE., 2017)
For years, pundits have trumpeted the earthshattering changes that big data and smart networks will soon bring to our cities. But what if cities have long been built for intelligence, maybe for millennia? In Code and Clay, Data and Dirt Shannon Mattern advances the provocative argument that our urban spaces have been smartand mediated for thousands of years. Offering powerful new ways of thinking about our cities, Code and Clay, Data and Dirt goes far beyond the standard historical concepts of origins, development, revolutions, and the accomplishments of an elite few. Mattern shows that in their architecture, laws, street layouts, and civic knowledge-and through technologies including the telephone, telegraph, radio, printing, writing, and even the human voice-cities have long negotiated a rich exchange between analog and digital, code and clay, data and dirt, ether and ore. Matterns vivid prose takes readers through a historically and geographically broad range of stories, scenes, and locations, synthesizing a new narrative for our urban spaces. Taking media archaeology to the citys streets, Code and Clay, Data and Dirt reveals new ways to write our urban, media, and cultural histories.